ANTESEDEN PENJUALAN ADAPTIF DAN PENGARUHNYA TERHADAP KINERJA TENAGA PENJUALAN - Kharisma, B. Meiga; Widiyanto, Ibnu (Diponegoro Journal of Management, 2015)
Salesperson plays an important role in supporting company’s success. By developing salesperson performance, it is expected that company’s performance will be developed as well. This research analyzes the factors that influence the increasing of salesperson performance, by developing variables such as learning orientation, customer orientation, and salesperson competencies. To discuss the problem, this research proposes research model with four constructs, 12 indicators, and five hypothesises. Those hypothesises were tested by distributing 240 questionaires with doing a census of the each salespeople at Nasmoco car dealer in Semarang. The data were analyzed using Structural Equation Modelling. The result of this analysis has fulfilled the Goodness of Fit Index criterias, X2 (chi square) 9.375, 0.284 (≥0.05), RMSEA 0.042(≤0.08), GFI 0.975 (≥0.90), AGFI 0.933 (≥0.90), TLI 0.996 (≥0.95), CFI 0.998 (≥0.95), it can be said that the model is appropriate. The testing of proposed hypothesises shows those three hypothesises has met the prescribed requirements CR>2 with probability level < 0.05.Based on the analysis, proposed theoretical implications, communication skills, customer orientation, and adaptive selling affect the salesperson performance proper with the theories background.